Surfing the net for software engineering notes. - Doernhoefer, Mark (Software engineering notes.)
Our last survey of Internet software security sites was about four years ago. I thought it was about time to take another look at the web to see what has been added in the last few years. Some of the sites we've visited before have added extensive new information and resources for developers working on secure software. And this time around, I'd like to focus on some open source software that can help you test and evaluate your applications.